Pengembangan Media Pembelajaran Flipbook pada Mata Pelajaran IPAS untuk Meningkatkan Hasil Belajar - Iliyani Eka Rahmawati; Ali Sunarso (Postgraduate, University of Mataram, 2024)
This study aims to develop learning media in the form of flipbooks to improve the learning outcomes of grade V elementary school students in IPAS (Natural and Social Sciences) subjects, focusing on material about what Indonesia looks like. This research method applies the ADDIE-type Research and Development (R&D) development model which consists of five research stages. Data analysis techniques applied in this study include initial data analysis with the normality test, as well as final data analysis using the T-Test and N-Gain test. The results of this study obtained a score of 94% from media experts and a score of 92% from material experts with very feasible criteria. The effectiveness of using flipbook media is done by calculating the results of pretest and post-test scores using the N-Gain test which obtained a score of 0.6541 which is included in the moderate category and paired sample t-test obtained results of 0.000 < 0.005 then Ho is rejected and Ha is accepted. These results indicate that flipbook media is feasible to use and can improve student learning outcomes.